Holistic Education through the Hiziban Tradition in Nahdlatul Wathan Madrasahs - Ala’ul Islam; L Pahrurrozi (PT. Anagata Sembagi Education, 2025)
Islamic education today tends to be cognitively centered and gives insufficient attention to the affective, emotional, and social dimensions of learners. The Hiziban tradition practiced in Nahdlatul Wathan madrasahs pedagogically demonstrates the capacity to integrate spiritual, moral, emotional psychological, and social dimensions as a framework of holistic education. This study employs a qualitative approach using a case study design. Data were collected through participatory observation, interviews with supervising teachers and students, and documentation. The data were analyzed thematically through processes of data reduction, data display, and conclusion drawing based on the dimensions of holistic education. The findings indicate that the Hiziban tradition functions as experiential learning rooted in habituation, internalization, and collective interaction. This model serves as an alternative to Islamic education that is overly focused on cognitive aspects. Therefore, the Hiziban tradition can be considered a contextual pedagogical reference that is grounded in local culture and effective in shaping students’ character within the framework of holistic education